The role of antimicrobial peptides in skin tumorigenesis - Marcinkiewicz, Małgorzata; Majewski, Sławomir (Dermatology Review/Przegląd Dermatologiczny, 2016)
Antimicrobial peptides (AMPs), known as “natural antibiotics”, are the first line of defense in humans as effector molecules of the innate immune system of the skin. They present activity against a broad spectrum of bacteria, fungi, parasites and enveloped viruses. An increasing number of studies report altered expression of AMPs in human cancers. Antimicrobial peptides such as human β defensins, human cathelicidin, ribonuclease 7 and psoriasin, a member of S100 proteins, are suggested to play a role in tumor progression and tumor suppression in pre-malignant skin lesions and malignancies. Noticeable changes in AMPs expression in skin tumorigenesis suggest a correlation between peptides and cutaneous cancers, though it is still a matter of discussion. In this article we review recent studies on the relationship between antimicrobial peptides and skin tumorigenesis.